Placing sound: a contextual exploration of personal identities in sound art discourse through performance art practice - Zeco, Maja (Robert Gordon University, 2019)
This practice-led research explores how personal identities shape listening experiences in the context of sound art discourse. The research aim is to develop a contextual approach to sound art practice, informed by personal experience of listening to place. These challenges are summed up in pieces of performance art that also highlight the interdisciplinary nature of sound art. The research questions are: 1) How do personal identities and histories shape our experience of listening to place, and how does this form of listening specifically inform approaches to sound art?; 2) How does the acknowledgment of context through the intrusion of place-based, identity-based approaches challenge the field of sound art?; 3) How can an artist negotiate the interdisciplinary challenge of music versus visual art approaches in sound art?; and 4) How and in what ways can performance art practice expand strategies of making, in the field of sound art practice? The critical literature review recognises the interdisciplinarity of sound art discourse (visual art, electroacoustic and soundscape composition), where compositional approaches (Chion; Schaeffer; Schafer) foster material-oriented tendencies in the field, shifting attention from the contextual - and personal - aspects of listening. The work of geographers (Rodaway, Massey and Tuan) forwards multisensory, contextual and migrant perspectives in this inquiry. Contemporary sound art theorists such as LaBelle historically map/scope the field, and Voegelin's concept of pathetic trigger and timespace is expanded and critically discussed. The research methods include soundwalking, field recording, taking photographs and interviewing selected residents in four places: Banchory and Aberdeen in Scotland, and Maglaj and Sarajevo in Bosnia and Herzegovina. Through the range of personal narratives, the research shows that personal identities shape the experience of listening to place, through mechanisms of autobiographical memory, informed by the context and history of places. In this process, the author's experience of growing up in post-conflict Sarajevo, along with her experience of migration to Scotland, offers contextual and personal insights. Sound art practice takes the form of performance art pieces in this work. This is a practice embodying histories and knowledges of place, acquired during the research and experience of soundwalks, while revisiting the contribution of performance art to sound art discourse.
Keywords: FOS: Arts (arts, history of arts, performing arts, music); FOS: Social and economic geography